The impact of petroleum on the balance of payments - Olufemi Fajana (Intereconomics, 1975)
Nigeria's transformation from a predominantly agricultural to an oil economy has had many significant social and economic effects. In this paper, an attempt is made to analyse one of such effects: the impact on the country's balance of payments.
Keywords: 330; Nigeria